YES Problem: a(b(x1)) -> b(b(b(x1))) a(c(x1)) -> c(b(b(x1))) b(a(x1)) -> a(a(a(x1))) b(c(x1)) -> c(c(c(x1))) a(x1) -> x1 b(x1) -> x1 c(x1) -> x1 Proof: String Reversal Processor: b(a(x1)) -> b(b(b(x1))) c(a(x1)) -> b(b(c(x1))) a(b(x1)) -> a(a(a(x1))) c(b(x1)) -> c(c(c(x1))) a(x1) -> x1 b(x1) -> x1 c(x1) -> x1 Bounds Processor: bound: 1 enrichment: match automaton: final states: {2,11,8,5,1} transitions: c0(2) -> 6* c0(12) -> 11* c0(6) -> 12* c1(27) -> 28* c1(17) -> 18* c1(21) -> 22* c1(19) -> 20* c1(18) -> 19* a0(2) -> 9* a0(10) -> 8* a0(9) -> 10* b0(3) -> 4* b0(4) -> 1* b0(6) -> 7* b0(2) -> 3* b0(7) -> 5* f30() -> 2* 27 -> 18* 19 -> 22,12,20 17 -> 18* 7 -> 27,5 12 -> 11* 28 -> 18* 4 -> 1* 11 -> 5* 2 -> 6,3,9 22 -> 18* 6 -> 21,12,7 21 -> 22* 8 -> 9,10 1 -> 7,5,3 20 -> 28,18,11 5 -> 6,7,12 9 -> 10* 3 -> 17,4 18 -> 19* 10 -> 8* problem: Qed